ACCOUNTING FOR LONG-TERM ASSETS BASED ON INTERNATIONAL STANDARDS: CORPORATE PRACTICES AND IMPLICATIONS - Kakhkharov Zukhriddin Zafarbek ogli (Scholar Express Journals, 2025)
This paper examines the accounting treatment of long-term assets in accordance with international financial reporting standards (IFRS), focusing on how companies apply these standards in practice and the implications for financial transparency and strategic decision-making. Long-term assets, such as property, plant, equipment, and intangible resources, represent a significant portion of enterprise value and require consistent, transparent accounting practices to ensure comparability and compliance in the global market. Drawing on a review of IFRS standards—particularly IAS 16 (Property, Plant and Equipment), IAS 38 (Intangible Assets), and IAS 36 (Impairment of Assets)—the paper analyzes the recognition, measurement, depreciation, revaluation, and impairment processes. It also evaluates corporate reporting practices using real-world examples from companies operating in diverse industries and jurisdictions. The findings indicate that while IFRS adoption has enhanced global consistency in asset accounting, variation still exists in the application of judgment-based elements such as useful life estimation, revaluation frequency, and impairment testing. The paper concludes by highlighting best practices, common challenges, and policy implications for improving the quality and reliability of long-term asset reporting under IFRS
Keywords: long-term assets; asset revaluation; depreciation